The Anti-Biofilm Efficacy of Caffeic Acid Phenethyl Ester (CAPE) In Vitro and a Murine Model of Oral Candidiasis - de Barros, Patrícia Pimentel [UNESP] (2021)
Candida albicans is the main fungal species associated with the development of oral candidiasis. Currently, therapeutic options for these infections are limited by the adverse effects of antifungal drugs and by the emergence of drug resistant strains. Thus, the development of new antifungal agents is needed for the prevention and treatment of oral Candida infections. Caffeic acid phenethyl ester (CAPE) is a natural compound from propolis polyphenolic groups that exhibits many pharmacological properties. In this study, we investigated whether CAPE can have antifungal and immunomodulatory effects on oral candidiasis. Preliminary tests to assess the antifungal activity of CAPE were performed using the Minimum Inhibitory Concentration (MIC) assay that demonstrated inhibition in a range from 16 to 32 μg/mL, confirming its antifungal activity on several C. albicans strains isolated from the oral cavity. Subsequently, we analyzed Candida spp biofilms formed in vitro, in which CAPE treatment at 5 x MIC caused a reduction of 68.5% in the total biomass and ~2.60 Log in the viable cell count (CFU/mL) in relation to the untreated biofilm (p<0.0001). Next, RNA was extracted from untreated and CAPE-treated biofilms and analyzed by real-time qPCR. A series of genes analyzed (ALS1, ECE1, EPA1, HWP1, YWP1, BCR1, BGR1, CPH1, EFG1, NDT80, ROB1, TEC1, UME6, SAP2, SAP5, PBL2, and LIP9) were downregulated by CAPE compared to the untreated control group (p<0.0001). In in vivo studies using Galleria mellonella, the treatment with CAPE prolonged survival of larvae infected by C. albicans by 44.5% (p < 0.05) and accompanied by a 2.07-fold increase in the number of hemocytes. Flow cytometry revealed the most prominent increases were in types P2 and P3 hemocytes, granular cells, which phagocytize pathogens. In addition, CAPE treatment decreased the fungal load in the hemolymph and stimulated the expression of antifungal peptide genes such as galiomicin and gallerimycin. The antifungal and immunomodulatory activities observed in G. mellonella were extended to a murine model of oral candidiasis, in which CAPE decreased the levels of C. albicans colonization (~2 log CFU/mL) in relation to the untreated control group. In addition, CAPE treatment significantly reduced pseudomembranous lesions, invasion of hyphae on epithelium surfaces, tissue damage and inflammatory infiltrate (p < 0.05). CAPE was also able to increase the expression of β-defensin 3 compared to the infected and untreated group by 3.91-fold (p < 0.0001). Taken together, these results show that CAPE has both antifungal and immunomodulatory effects, making it a promising natural antifungal agent for the treatment and prevention of candidiasis and shows impact to oral candidiasis.